Curcuphenol possesses an unusual histone deacetylase enhancing activity that counters immune escape in metastatic tumours - Ellis, Samantha L. S.; Dada, Sarah; Nohara, Lilian L.; Saranchova, Iryna; Munro, Lonna; Pfeifer, Cheryl G.; Eyford, Brett A.; Morova, Tunc; Williams, David E.; Cheng, Ping; Lack, Nathan A.; Andersen, Raymond J.; et al. (Frontiers in Pharmacology, 2023)
A common component of culinary spices, curcuphenol, also found in marine invertebrates and plants, has been identified as a novel candidate for reversing immune escape by restoring expression of the antigen presentation machinery (APM) in cancer cells, thereby resurrecting the immune recognition of metastatic tumours. Two new synthetic curcuphenol analogues, that demonstrated consistent induction of MHC-I expression, were prepared by informed design and found to possess an unreported histone deacetylase (HDAC)-enhancing activity, altering epigenetic H3K27ac marks that induce APM component gene expression in both metastatic prostate and lung carcinoma cells. Intriguingly, the H3K27ac ChIPseq analysis of curcuphenol-treated cells reveals that the induced epigenomic marks closely resemble the changes in genome-wide pattern observed with interferon-γ, a recognized physiological immune modifier, underscoring the possible implications of dietary components and their analogues in modulating immune responses.